2005
DOI: 10.1093/rpd/nci323
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose from coal slag used as building material in the Transdanubian region of Hungary

Abstract: Coals mined in the Transdanubian region in Hungary have an elevated concentration of (226)Ra, which becomes enriched in the slag after burning. This slag has been used as filling and/or insulating material in building works. The aim of this study was to investigate the radiological situation in this territory in terms of the possible impact of this residual material from coal. Flats in three towns with a coal mine and a coal-fired power plant operating in their neighbourhood were examined. The radionuclide con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The radon/thoron exhalation greatly depends on the characteristics of the sample. The survey of radon exhalation from various media, such as building materials, soils, and by--products, is common [4][5][6][7][8][9][10][11][12][13], while thoron is of less interest owing to its complicated measurement technique and presumably, its less signifi cant dose contribution. Owing to signifi cantly lower diffusion length of thoron than radon, in general, thoron could be an indoor problem only when the source is present in the building material.…”
Section: Introductionmentioning
confidence: 99%
“…The radon/thoron exhalation greatly depends on the characteristics of the sample. The survey of radon exhalation from various media, such as building materials, soils, and by--products, is common [4][5][6][7][8][9][10][11][12][13], while thoron is of less interest owing to its complicated measurement technique and presumably, its less signifi cant dose contribution. Owing to signifi cantly lower diffusion length of thoron than radon, in general, thoron could be an indoor problem only when the source is present in the building material.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies have been conducted to assess the feasibility and sustainability of their reuse as components in building materials, typically in cements and ceramics. In several countries, assessments of the radiological impact arising from the use of materials such as Bayer's process bauxite residue (red mud), fly/bottom ashes, etc., are being carried out [40,39,22,38,45]. The aim of this paper is to provide an overview of the radiometric content of residues and by-products used in building material production.…”
Section: Introductionmentioning
confidence: 99%
“…A very large scatter of data for radionuclide content in fly ash can be found between different countries (Nuccetelli et al, 2015) and only limited data can be found for Serbian fly ash (Kisic et al, 2013). Several studies found that the natural radionuclide content in fly ash can be significantly high (Somlai et al, 1999(Somlai et al, , 2006Petropoulos et al, 2002;Stojanovska et al, 2010). Therefore, utilization of FA as a supplementary material in cement production can cause a dose contribution to residents as a result of bulk inbuilt of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…It can increase in poorly ventilated areas, such as mines or even in buildings. Generally the underlying soil is the most dominant indoor radon enhancing factor (Szabo et al, 2014) in the case of lower floors or single storey buildings except in extreme cases when the building materials may be the main source (Somlai et al, 1999(Somlai et al, , 2006). Despite of the elevated level of 226 Ra FA has a relatively low emanation coefficient which can be beneficial for HVFAC from a radon exhalation point of view (Kovler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%